ЛЕГКИЙ ПРИМЕР!!!!!!!!!!!!!!!!!!!!!!!!!!!! [latex]( \frac{x}{x-2} - \frac{x}{x+2} - \frac{x^2+4}{4-x^2} ) : \frac{2x+x^2}{(2-x)^2} [/latex]

ЛЕГКИЙ ПРИМЕР!!!!!!!!!!!!!!!!!!!!!!!!!!!! [latex]( \frac{x}{x-2} - \frac{x}{x+2} - \frac{x^2+4}{4-x^2} ) : \frac{2x+x^2}{(2-x)^2} [/latex]
Гость
Ответ(ы) на вопрос:
Гость
1)x/(x-2)-x/(x+2)+(x²+4)/(x-2)(x+2)=(x²+2x-x²-2x+x²+4)/(x²-4)= =(x²+4x+4)/(x²-4)=(x+2)²/(x-2)(x+2)=(x+2)/(x-2) 2)(x+2)/(x-2)*(x-2)²/x(2+x)=(x-2)/x
Не нашли ответ?
Ответить на вопрос
Похожие вопросы